Laparoscopic repair of segmental obturator nerve injury defect using an artificial nerve conduit: A case report. Issue 11 (14th July 2021) - Matsumoto, Tsuyoshi; Banda, Chihena H.; Kondo, Eiji; Yoshida, Kenta; Hirata, Toru; Ikeda, Tomoaki; Narushima, Mitsunaga
Abstract: Obturator nerve injury is an uncommon complication frequently associated with pelvic gynecologic or urologic cancer surgery. It can lead to disability or adversely affect quality of life. Large segmental defects are particularly difficult to manage as the limited mobility of the nerve prevents tension‐free direct end‐to‐end anastomosis. A 36‐year‐old woman with cervical cancer underwent sentinel lymph node biopsy, laparoscopic radical hysterectomy, and bilateral adnexectomy. During the procedure, the sentinel lymph node (right obturator node) adherent to the obturator nerve was resected together with the nerve segment leaving a 3 cm defect. Immediate laparoscopic obturator nerve repair was performed using an artificial nerve conduit leading to successful recovery. We report this unique case due to rarity of large segmental obturator nerve defects and present laparoscopic nerve repair with artificial nerve conduits as a useful treatment alternative of these important injuries, without nerve donor site morbidity.